Early evidence and lessons learnt from an NHS Wales Video Consulting Service. (2nd April 2022) - Johns, Gemma; Khalil, Sara; Ogonovsky, Mike; Hesseling, Markus; Wardhaugh, Allan; Phipps, Kerrie; Williams, Jessica; Whistance, Bethan; Ahuja, Alka
Background: The use of video consulting (VC) in Wales, United Kingdom (UK) has expanded rapidly during the COVID-19 pandemic. Traditionally, VC has been the subject of small-scale projects and evaluations. In response to the pandemic emergency, there was an opportunity to roll out and evaluate VC on a larger and more representative scale, across a wider range of National Health Service (NHS) specialities. Aims: This paper presents an overview of a dataset captured by the 'The NHS Wales VC Service'. The purpose of this study was to capture perspectives of healthcare professionals only (including clinicians, administration and management) on the use of VC and explore lessons learnt from the national implementation process. Methodology: Using an online, mixed methods retrospective survey capturing descriptive and narrative data. Results: A total of 1256 NHS healthcare professionals shared their VC experience. Overall, responses were positive, and healthcare professionals expressed optimistic views regarding the use, value and benefit of VC, even when faced with challenges on occasions. Conclusions: A lesson learnt, is that difference occurs in innovation, even in a small country like Wales, yet it is not necessarily a negative outcome, but rather, respecting and incorporating difference, can improve long-term sustainability.